April 1967 River Hill Gets Out of Hole! Newspaper Clipping - River Hill Missionary Baptist Church (Valdosta State University Archives and Special Collections, 2026, 1967)
This newspaper article helped me locate the 1901 deed and the March 1967 deed. It mentioned T.S. McKey deeding property to the church at the turn of the century to build their first church. It is later mentioned that the church was moved by church trustees and J.D. McKey a month before the article was published. The church was moved to the current location because I-75, built six years prior, had left River Hill in an undesirable location. The church used the move as an opportunity to update its facilities with the help of J.D. McKey.
PDF
Keywords: River Hill Missionary Baptist Church (Valdosta, Ga.); Baptist churches; African American Baptists